A review: algorithm used for beam forming systems - Pal, Soma; Haque, Azazul (International Journal of Engineering and Technology, 2017)
Wireless communication uses a smart antenna to provide better coverage and capacity for the communication system. Main functions performed by the smart antenna are Direction of Arrival estimation (DOA) and beamforming (DBF). The beam forming is signal processing techniques which combine antenna array technology with high-performance up/down-conversion, analog to digital conversion and digital signal processing to provide receivers with very high spatial selectivity. This paper evaluates non-blind algorithm such as LMS, to compute the weight calculation for phased array antenna using Matlab Simulink.
Keywords: DOA; Beam forming; LMS and Weight calculation.